Stem Cell-Derived Exosomes as a Therapeutic Option for Spinal Cord Injuries; a Systematic Review and Meta-Analysis - Jabermoradi, Sajjad; Paridari, Parsa; Adel Ramawad, Hamzah; Gharin, Pantea; Roshdi, Shayan; Toloui, Amirmohammad; Yousefifard, Mahmoud (Archives of Academic Emergency Medicine, 2024)
Introduction: Exosomes function as cell signaling carriers and have drawn much attention to the cell-free treatments of regenerative medicine. This meta-analysis aimed to investigate the efficacy of mesenchymal stem cell-derived (MSC-derived) exosomes in animal models of spinal cord injuries (SCI). Method: A comprehensive search was conducted in Medline, Embase, Scopus, and Web of Science to attain related articles published by January 31, 2023. The eligible keywords were correlated with the spinal cord injury and MSC-derived exosomes. The evaluated outcomes were locomotion, cavity size, cell apoptosis, inflammation, neuro-regeneration, and microglia activation. A standardized mean difference was calculated for each sample and a pooled effect size was reported. Results: 65 papers fully met the inclusion criteria. Treatment with MSC-derived exosomes ultimately improved locomotion and shrunk cavity size (p<0.0001). The administration of MSC-derived exosomes enhanced the expression of beta-tubulin III, NF200, and GAP-43, and increased the number of NeuN-positive and Nissl-positive cells, while reducing the expression of glial fibrillary acidic protein (p<0.0001). The number of apoptotic cells in the treatment group decreased significantly (p<0.0001). Regarding the markers of microglia activation, MSC-derived exosomes increased the number of CD206- and CD68-positive cells (p=0.032 and p<0.0001, respectively). Additionally, MSC-derived exosome administration significantly increased the expression of the anti-inflammatory interleukin (IL)-10 and IL-4 (p<0.001 and p=0.001, respectively) and decreased the expression of the inflammatory IL-1b, IL-6, and TNF-a (p<0.0001). Conclusion: MSC-derived exosome treatment resulted in a significantly improved locomotion of SCI animals through ameliorating neuroinflammation, reducing apoptosis, and inducing neuronal regrowth by facilitating a desirable microenvironment.